2021
DOI: 10.1177/2192568221991124
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Lumbar Disk Herniation Surgery in the Dutch Population

Abstract: Study Design: Retrospective cohort study. Objective: There is only limited data on the outcome of primary surgery of lumbar disk herniation (LDH) in Dutch patients. The objective of this study is to describe undesirable outcomes after primary LDH. Methods: The National Claims Database (Vektis) was searched for primary LDH operations performed from July 2015 until June 2016, for reoperations within 18 months, prescription of opioids between 6 to 12 months and nerve root block within 1 year. A combined outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Prospective cohort studies have shown that most patients experience a clinically relevant improvement in pain and disability after lumbar radiculopathy following microdiscectomy, supporting the role of surgery and suggesting a favorable average course [27]. However, many patients do not fit the average trajectory profile and for some, the outcomes result in serious complications and/or long-term, persistent problems [18,27,29]. Therefore, this study aimed to explore the variability in recovery after lumbar microdiscectomy and post-operative physiotherapy by deriving and predicting outcome trajectories.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Prospective cohort studies have shown that most patients experience a clinically relevant improvement in pain and disability after lumbar radiculopathy following microdiscectomy, supporting the role of surgery and suggesting a favorable average course [27]. However, many patients do not fit the average trajectory profile and for some, the outcomes result in serious complications and/or long-term, persistent problems [18,27,29]. Therefore, this study aimed to explore the variability in recovery after lumbar microdiscectomy and post-operative physiotherapy by deriving and predicting outcome trajectories.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, prior back surgery was an important predictor for the poor outcome trajectories of pain and disability in comparison with the large improved trajectory. Previous research shows there is a high risk of reoperations (0.6-24%) for patients who underwent lumbar discectomy and more than half of these patients undergo reoperation within the first two years [1,15,16,29]. Consequently, worse outcomes are reported for patients requiring multiple lumbar spine operations [16,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This offers the opportunity to analyze nationwide claims data within the centrally registered National Claims Database (Vektis) in which all insurance companies in the Netherlands take part. This approach has been successful in the past for quality assessment in myocardial infarction, chemotherapy and intensive care unit admissions in upper gastrointestinal cancer patients, as well as other diseases [19][20][21][22], resulting in the identification of new quality indicators. In 2018, Schepens et al evaluated the post-RP UI rate based on the claims of absorbing pads [23].…”
Section: Introductionmentioning
confidence: 99%
“…Degenerative intervertebral changes of the lumbar spine with concomitant herniation of lumbar disks represent one of the most common reasons for lower back pain and the principal cause for spinal surgery [ 1 , 2 ]. Considering that the vast majority of people sustain an episode of lower back pain once during their lifetime, early detection and treatment initiation are essential to avoid high treatment costs and poor outcome [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%